The mediating role of emotional intelligence in the relationship between resilience and workplace violence competence among nursing students - Shaimaa Mohamed Amin; Doaa El Demerdash; Ahmed Abdelwahab Ibrahim El-Sayed; Ahmed Abdellah Othman; Mohamed Hussein Ramadan Atta; Ali Albzia; Mahitab Mohamed Abdelrahman; Haitham Mokhtar Mohamed Abdallah; Ibrahim Alasqah; Shadia Ramadan Morsy Mohamed (BMC Nursing)
Abstract Background Nursing students encounter workplace violence during clinical practice, which poses challenges to their resilience and competence in managing such situations. Emotional intelligence plays a crucial role in how students navigate these challenges, potentially mediating the relationship between resilience and workplace violence competence. Aim The primary aim of this study was to evaluate the mediating role of emotional intelligence in the relationship between resilience and the competence to manage workplace violence among nursing students. Methods A cross-sectional descriptive design was employed, with 500 undergraduate nursing students from Sohag University participating in the study. Data were collected using three validated scales: the Trait Meta-Mood Scale (TMMS-24) to assess emotional intelligence, the Connor-Davidson Resilience Scale (CD-RISC-10) to measure resilience, and the Management of Workplace Violence Competence Scale (MWVCS) to evaluate competence in managing workplace violence. Data were analyzed using Pearson’s correlation and mediation analysis via JASP software. Results Significant positive correlations were found between emotional intelligence and resilience (r = 0.42, p < 0.001), emotional intelligence and workplace violence competence (r = 0.38, p < 0.001), and resilience and workplace violence competence (r = 0.44, p < 0.001). Mediation analysis revealed that emotional intelligence partially mediated the relationship between resilience and workplace violence competence (indirect effect = 0.12, 95% CI [0.08, 0.17]). Conclusion The findings highlight the importance of emotional intelligence and resilience in enhancing nursing students’ competence in managing workplace violence. Developing emotional intelligence may be a valuable strategy for improving students’ resilience and readiness to handle challenging clinical environments. Educational programs should consider integrating emotional intelligence training to better equip nursing students for clinical practice. Clinical trial number Not applicable.